Investigation the Role of miR-506 in Metformin-Induced Cell Death Mechanism in MCF-7 and MDA-MB-231 Breast Cancer Cells - RENCÜZOĞULLARI, ÖZGE; QAYOUMI, SURAYA (Manisa Celal Bayar Üniversitesi Fen Bilimleri Enstitüsü, 2024)
Micro RNAs (miRNA) play a role in basic cellular processes such as cell growth, development, cell cycle and apoptosis by affecting gene expression. Abnormal regulation or changes in expression of miRNAs can be observed in many diseases, especially cancer. Therefore, miRNAs are also being investigated as potential therapeutic targets. It has been suggested that miR-506 may be expressed at low levels in various types of cancer and this may contribute to cancer development. In this study, the effect of miR-506 on the sensitivity of breast cancer cells to metformin was evaluated in terms of its effect on cell survival and apoptotic mechanism. Metformin caused a dose-dependent decrease in cell viability and induced loss of mitochondrial membrane potential in MCF-7 cells while MDA-MB-231 cells were more resistant. The colony formation and migration potential of both cell lines with increased miR-506 expression were significantly suppressed after metformin treatment. Additionally, apoptotic cell death triggered by metformin was induced in both cell lines when miR-506 expression was increased. In conclusion, miR-506 acts as a tumor suppressor in MCF-7 and MDA-MB-231 cells and increases their sensitivity to metformin, indicating the potential of miR-506 to be an important therapeutic target in future studies.
Keywords: Apoptotic Cell Death; Breast Cancer; Metformin; miR-506